Performance of social marketing in reaching the poor and vulnerable in AIDS control programmes - Price, Neil (2001)
Reviews evidence on the impact and effectiveness of condom social marketing programmes (CSMPs) in reaching the poor and vulnerable with information, services and products in the context of HIV/AIDS/STD prevention and control. Assesses the extent to which social marketing is effective in improving access for the poor and vulnerable using a number of variables.